Playing games to strengthen groundwater governance in rural India - Meinzen-Dick, Ruth S.; Bruns, Bryan Randolph; Sanil, Richu (CGIAR System Organization, 2022)
This blog post summarises the online seminar, NEXUS Gains Talk 6.